2016
DOI: 10.1515/hukin-2015-0146
|View full text |Cite
|
Sign up to set email alerts
|

Within-Session Stability of Short-Term Heart Rate Variability Measurement

Abstract: The primary aim of this study was to assess the retest stability of the short-term heart rate variability (HRV) measurement performed within one session and without the use of any intervention. Additionally, a precise investigation of the possible impact of intrinsic biological variation on HRV reliability was also performed. First, a single test-retest HRV measurement was conducted with 20-30 min apart from one another. Second, the HRV measurement was repeated in ten non-interrupted consecutive intervals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
5
10
0
3
Order By: Relevance
“…We came across only one study that it looked within session stability of HRV measures in resting position like our study. According to the ICC analysis of two sessions, that made in the 20‐min break, LF and HF powers’ reliability was almost in the good (ICC 0·59) and excellent (ICC 0·86) level, respectively (Cipryan, ).…”
Section: Discussionmentioning
confidence: 99%
“…We came across only one study that it looked within session stability of HRV measures in resting position like our study. According to the ICC analysis of two sessions, that made in the 20‐min break, LF and HF powers’ reliability was almost in the good (ICC 0·59) and excellent (ICC 0·86) level, respectively (Cipryan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been recommended that both time domain and frequency domain statistics be incorporated when analysing HRV, the two statistical methods correlate with one another to such a strong degree that they can be used as surrogates for each other . Further, time domain methods, particularly RMSSD (defined below), have been shown to have greater reliability when measuring short‐term HRV than frequency domain methods. The following conventional time domain methods of analysing HRV were therefore selected for this study (for formulas see Appendix S1 , supporting information): the square root of the mean sum of squares of ΔRR intervals (RMSSD) and standard deviation of RR intervals (SDNN).…”
Section: Methodsmentioning
confidence: 99%
“…Reliability of ln RMSSD in 10 consecutive 5‐min trials reported an average typical error of 0.20 (90% CI: 0.18; 0.22) and a coefficient of variation of 9.9% (8.8; 11.3) in healthy young participants. Importantly, the typical error as a result of biological variation was deemed trivial, having no significant impact on HRV reliability (Cipryan, 2016). Silvetti et al (2001) further support the use of RMSSD in their review of HRV in healthy children and adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of HRV research has been conducted in clinical populations, removed from real‐life situations, which makes the generalizing of findings to nonclinical cohorts unjustified. Consideration must be given to the susceptibility of HRV testing to variations in measurement, particularly with retesting days and months post first assessment (Cipryan, 2016). Variations include factors such as age (adolescents have a greater range of beat‐to‐beat variation than older participants), gender, state of alertness, obesity, fitness levels (participants who regularly exercise have associated lower heart rate and higher HRV), smoking and drinking status (participants who smoke or drink regularly show higher heart rate and lower HRV) (Hammoud et al, 2018; Sharma & Gedeon, 2012).…”
Section: Introductionmentioning
confidence: 99%